Experimental Synthesis and In Vivo Assessment of the Antidiabetic Activity of an Iron(III)-Glycine Complex - Valencia, Pinkan; Ambarwati, Yuli; Nurhasanah, Nurhasanah; Widiarto, Sonny; Setiawan, Andi; Pandiangan, Kamisah Delilawati (Jurnal Kartika Kimia, 2025)
Indonesia is one of the countries with a growing number of diabetes mellitus cases each year. This disease can cause damage to vital organs such as the liver, pancreas, kidneys, and heart. Type 1 diabetes is generally treated with insulin, while type 2 diabetes is commonly managed with oral medications. Recently, metal complexes have emerged as promising alternatives for antidiabetic therapy. Among these, iron(III) complexes are of interest, although research on Fe(III) complexes remains limited. This study aims to synthesize and evaluate the in vivo antidiabetic activity of an iron(III)-glycine complex. The synthesized complex appeared as an orange-brown solid with a yield of 95.02% and a sample mass of 0.267 g. UV-Vis spectrophotometric analysis showed absorption peaks at 210, 224, and 305 nm, indicating the presence of the Fe(III)-glycine complex. FTIR analysis revealed characteristic absorption bands corresponding to Fe–O at 523 cm⁻¹ and Fe–N at 823 cm⁻¹. In vivo tests were conducted on mice induced with alloxan. Body weight of the mice decreased after induction but stabilized after treatment during the third and fourth weeks. The highest reduction in blood glucose levels was observed at a dose of 200 μg/kg body weight, with a 68% decrease. These results suggest that the Fe(III)-glycine complex exhibits potential as an antidiabetic agent.